The Unequal Effect of India's Industrial Liberalization on Firms' Decision to Innovate: Do Business Conditions Matter?1. (16th April 2018) - Bas, Maria; Paunov, Caroline
Abstract : Product‐market competition can boost industry growth if firms invest more in innovation. Using a natural policy experiment, the removal of India's License Raj, we show that firms in liberalized industries were 9% more likely to invest in R&D than firms in non‐liberalized industries. However, the impacts were not the same across firms of different size. After the reforms, firms in the top quartile were 23% more likely to invest in R&D than those in the lowest size quartile. Both productivity differences across firms and the heterogeneous impacts of business conditions on firms explain unequal effects of India's industrial liberalization reform.